RAVE stars in K2: I. Improving RAVE red giants spectroscopy using asteroseismology from K2 Campaign 1 - Valentini, Marica; Boeche, Corrado; Grebel, Eva K. (Arxiv, 2016)
We present a set of 87 RAVE stars with detected solar like oscillations, observed during Campaign 1 of the K2 mission (RAVE K2-C1 sample). This dataset provides a useful benchmark for testing the gravities provided in RAVE Data Release 4 (DR4), and is key for the calibration of the RAVE Data Release 5 (DR5). In the present work, we use two different pipelines, GAUFRE (Valentini et al. 2013) and Sp_Ace (Boeche & Grebel 2016), to determine atmospheric parameters and abundances by fixing log(g) to the seismic one. Our strategy ensures highly consistent values among all stellar parameters, leading to more accurate chemical abundances. A comparison of the chemical abundances obtained here with and without the use of seismic log(g) information has shown that an underestimated (overestimated) gravity leads to an underestimated (overestimated) elemental abundance (e.g. [Mg/H] is underestimated by ~0.25 dex when the gravity is underestimated by 0.5 dex). We then perform a comparison between the seismic gravities and the spectroscopic gravities presented in the RAVE DR4 catalogue, extracting a calibration for log(g) of RAVE giants in the colour interval 0.50<(J - Ks)<0.85. Finally, we show a comparison of the distances, temperatures, extinctions (and ages) derived here for our RAVE K2-C1 sample with those derived in RAVE DR4 and DR5.DR5 performs better than DR4 thanks to the seismic calibration, although discrepancies can still be important for objects for which the difference between DR4/DR5 and seismic gravities differ by more than ~0.5 dex. The method illustrated in this work will be used for analysing RAVE targets present in the other K2 campaigns, in the framework of Galactic Archaeology investigations.